Effect of Mitochondrial DNA T15663C Mutation on Type 2 Diabetes Mellitus and Cataract Patients, Molecular Dynamics Simulation Study - Rahmadanthi, Fanny Rizki; Fariz Maulana, Ahmad; Destiarani, Wanda; Gaffar, Shabarni; Maksum, Iman Permana (Trends in Sciences, 2024)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia. Type 2 diabetes mellitus patients are known to have mutations in their mitochondrial DNA (mtDNA). mtDNA easily undergoes mutations because it does not have histone proteins for protection and lacks a proofreading mechanism during its replication. The mtDNA mutations T15663C found in type 2 diabetes mellitus patients sufferers with a cataract disease. This mutation was found to occur in the cytochrome b gene, one of the gene in the complex III respiratory chain. In this study we investigate the effect of this mutation on the structure of cytochrome b using molecular dynamics simulations using PDB ID: 5XTE as a template and carrying out simulations for 250 ns. The models of wild type and mutant protein structure were constructed using CHARMM-Gui so that, the protein was looked like in the mitochondrial membrane. The results of the molecular dynamics simulation show that the potential energy of the wild type model is lower than the mutant model, the RMSD value of the wild type model is more stable at 114 - 180 ns, and the RMSF value in the wild type model does not fluctuate as much as the mutant model. In addition, the hydrogen bond (H bond) analysis of the mutant model has a higher H bond number than the wild type model, which means that the mutant model is more rigid. The simulation results were visualized using VMD, and new hydrogen bonds were found in the mutant model. HIGHLIGHTS Mitochondrial mutations can lead to many diseases such as type 2 diabetes mellitus and cataracts. Molecular dynamics simulations can be used to see the differences between wild type and mutant structures. Potential energy, Root Mean Square Deviation (RMSD), Root Mean Square Fluctuation (RMSF) and hydrogen bond (H bond) analysis commonly used to analyze simulation results, such as the stability or rigidity of the structure. GRAPHICAL ABSTRACT